Lithium-Silicon Compounds as Electrode Material for Lithium-Ion Batteries. Issue 13 (28th September 2020) - Uxa, Daniel; Hüger, Erwin; Dörrer, Lars; Schmidt, Harald
Abstract : The element silicon is currently considered as one of the most promising alternative electrode materials for lithium-ion batteries. During lithiation, silicon experiences a large volume increase, which often leads to material failure and significant irreversible loss of capacity. The production of amorphous thin layers of lithium-silicon compounds as pre-lithiated electrode material is a promising approach to reduce significant capacity losses and to "homogenize" volume expansion. We demonstrate that it is possible to produce stable amorphous lithium-silicon thin films with variable stoichiometry using ion beam co-sputtering. The electrochemical experiments show that the different starting compositions of the electrode material (different x for Lix Si) compared to pure amorphous silicon cause significant differences in the electrochemical behavior and in the electrode kinetics. With an increasing amount of lithium in the lithium-silicon electrode, the specific charge and discharge capacity decreases, but irreversible capacity losses are reduced in the first cycle and the Coulomb efficiency stabilizes at a value of almost 100%. Thin films with a low Li concentration, such as Li0.06 Si, are likely not stable to the lithiation process during long term cycling due to material failure, whereas Li0.4 Si shows a much better charge/discharge stability up to 100 cycles.